Pengaruh Model Pembelajaran Problem Based Learning Berbasis Experimen Sederhana dalam Pengenalan Sains Anak Usia Dini - Harahap, Arizky Insyirah; Sit, Masganti; Basri, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Problem-solving and critical thinking in early childhood can be done by carrying out science introduction activities. This study aims to determine the effect of a simple experiment-based problem-based learning model in the introduction of early childhood science. The type of research used is a ranking pre-experimental design using an intact group comparison design. The class was chosen randomly, with 6 children in the control group and 6 children in the experimental group. Based on the results of the study, it was shown that the simple experiment-based problem-based learning model for early childhood could be done by recognizing liquid objects such as sinking, floating, soluble and insoluble, and the properties of liquids. The simple experiment-based problem-based learning model is very influential in the introduction of early childhood science, where children think critically and can form new ideas by solving a problem.